The glass universe : how the ladies of the Harvard Observatory took the measure of the stars - Sobel, Dava (New York, New York : Viking, 2016)
The little-known true story of the unexpected and remarkable contributions to astronomy made by a group of women working in the Harvard College Observatory from the late 1800s through the mid-1900s.--
In the mid-nineteenth century, the Harvard College Observatory began employing women as "human computers" to interpret the observations their male counterparts made via telescope each night. As photography transformed the practice of astronomy, the ladies turned from computation to studying the stars captured nightly on glass photographic plates. The support of Mrs. Anna Palmer Draper, the widow of a pioneer in stellar photography, enabled the women to discern what stars were made of, divide the stars into meaningful categories for further research, and find a way to measure distances across space by starlight. Sobel tells the hidden history of the women whose contributions to the burgeoning field of astronomy forever changed our understanding of the stars and our place in the universe
Part one: The colors of starlight. Mrs. Draper's intent ; What Miss Maury saw ; Miss Bruce's largesse ; Stella nova ; Bailey's picture from Peru -- Part two: Oh, be a fine girl, kiss me!. Mrs. Fleming's title ; Pickering's "harem" ; Lingua franca ; Miss Leavitt's relationship ; The Pickering fellows -- Part three: In the depths above. Shapley's "kilo-girl" hours ; Miss Payne's thesis ; The Observatory Pinafore ; Miss Cannon's prize ; The lifetimes of stars -- Some highlights in the history of the Harvard College Observatory -- A catalogue of Harvard astronomers, assistants, and associates
Includes bibliographical references and index
Keywords: Harvard College Observatory; Harvard College Observatory; 1800-1999; Women in astronomy -- Massachusetts -- History; Women mathematicians -- Massachusetts -- History; Astronomy -- History -- 19th century; Astronomy -- History -- 20th century; Astronomy; Women in astronomy; Women mathematicians; HISTORY / Modern / 20th Century; SCIENCE / Astronomy; SCIENCE / History; SCIENCE / History; SCIENCE / Astronomy; HISTORY / Women; Massachusetts; History